Study of Lower Respiratory Tract Infections in Children in a Tertiary Care Hospital - Tahir Mehmood, Kulsoom, Rabia, Wahid, Ume Kalsoom, Asma Asghar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was designed to evaluate the efficacy of ultrasound and chest Xray among children with low respiratory tract infection. Place and Duration: POF Hospital Wah Cantt from September2020 to June 2021 Study type: Case control study Methodology: Children diagnosed with symptoms of respiratory distress, persistent cough, prolonged fever, abnormal auscultatory findings, and acute wheezes were included. Chest X-ray of frontal view was performed in antero-posterior lie-down or posteroanterior upright view depending on the age of the patients. To avoid unnecessary radiations lateral radiographs were not performed.A chest X-ray was performed to report inflammatory infiltrate, pneumothorax, Interstitial infiltrates, and lung hyper expansion. Meanwhile, a sonography examination was performed to diagnose Small subpleural consolidations < 10 mm in diameter, Interstitial syndrome –B7 lines Results: All the patients reported cough however, the persistent cough was reported in 11% of cases. Regarding chest, x-ray current work found consolidation in 68% along with 20% interstitial infiltrates in pneumonia cases. Patients with bronchiolitis had interstitial infiltrates in 50% of cases and lung hyper-expansion in 20% of cases. Conclusion: Our results concluded that chest ultrasound has better sensitivity and specificity for the diagnosis of pneumonia and bronchiolitis than a chest X-ray. Ultrasound can easily detect the small consolidations and numerous B lines than chest X-ray. Hence, chest ultrasound can be used as an alternative method for diagnosing lower respiratory tract infection.